Dynamic Capabilities in Young Innovative Firms: A Multiple-Case Study in Poland - Adam CZARNOTA (Communications of International Proceedings, 2023)
The purpose of this article is to identify the role of dynamic capabilities in newly innovative firms and present their impact on new ventures’ survival and growth. The study is of a empirical type. The research method is a multiple-case study based on 10 cases. Ten in-depth interviews were conducted with the founders of selected companies. Case analysis indicate the impact of dynamic capabilities on the ability to identify opportunities and threats, resource acquisition, and innovative performance. The results of the study show that dynamic capabilities represent a potential benefit for young innovative firms, enabling them to shape, integrate, and reconfigure essential resources to adapt to the environment, ultimately increasing their chances of survival, growth, and internationalisation.
Keywords: dynamic capabilities; innovation; new venture